Characteristics of Dapagliflozin Responders: A Longitudinal, Prospective, Nationwide Dapagliflozin Surveillance Study in Korea - Han, Eugene (Diabetes Ther, 2018)
INTRODUCTION: Sodium glucose co-transporter 2 (SGLT2) inhibitors, such as dapagliflozin, have demonstrated favorable effects in patients with type 2 diabetes (T2D). However, there are limited reports in the literature regarding the glucose-lowering effects of SGLT2 inhibitors in actual clinical settings. METHODS: The post-marketing surveillance data from a longitudinal prospective study of 2007 patients with T2D who were prescribed dapagliflozin (10 mg/day) were analyzed (ClinicalTrials.gov, NCT02252224). RESULTS: After 12 weeks of dapagliflozin treatment, glycated hemoglobin (HbA1c) and body mass index were significantly decreased (P < 0.001) from 8.1 ± 1.3% to 7.5 ± 1.2% and from 28.1 ± 4.4 to 27.6 ± 4.2 kg/m(2), respectively. Both body weight and HbA1c were reduced in 67.7% of patients, and HbA1c was lowered in 75.1%. Younger age, male sex, shorter diabetes duration, higher baseline HbA1c and estimated glomerular filtration rate (eGFR), and having dapagliflozin as add-on therapy were associated with stronger HbA1c reductions after dapagliflozin use (all P < 0.05). Moreover, subgroup analysis of eGFR of subjects with renal hyperfiltration (eGFR ≥ 120 ml/min/1.73 m(2)) showed the largest reduction in glucose level (% change, − 9.5; 95% CI − 6.8 to − 12.3 for HbA1c; P < 0.001). Multivariable logistic regression analysis showed that recent T2D diagnosis and higher HbA1c at baseline in patients who received an add-on regimen of dapagliflozin were statistically significantly associated with a dapagliflozin response (all P < 0.05). CONCLUSIONS: Dapagliflozin provides benefits for glycemic control and body weight. Patients in a relatively early stage of the course of diabetes with renal hyperfiltration might be more suitable for and gain maximal benefit from dapagliflozin treatment. TRIAL REGISTRATION: ClinicalTrials.gov identifier, NCT02252224. FUNDING: AstraZeneca. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s13300-018-0470-9) contains supplementary material, which is available to authorized users.